PELAYANAN KONSELING MULTI BUDAYA DI PONDOK PESANTREN - Shadiqatunil Aqwal; Yeni Karneli; Mudjiran Mudjiran (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
Islamic boarding school is a place where students learn the knowledge of Islamic religion, Islamic boarding school has a characteristic with the term mondok or can be known as living in a dormitory. Santri from different regions have diverse cultures, make santri as a pluralistic society, respect pluralism and enable diversity to remain sustainable, with other meanings communities accepting integration as a common way to deal with cultural diversity, but still displaying their identity . This research aims to find out how multicultural counseling services in the Nurul Yaqin Islamic Boarding School which have students from outside the area, bring their respective cultures, so that they have cultural differences between BK teachers and students. Where multicultural counseling is a helping process that emphasizes the balance between the theory and practice of counseling in accepting and valuing kultutal santri or clients. This research was conducted using descriptive qualitative research methods. Based on the results of this study it can be concluded that the multi-cultural counseling service at Nurul Yaqin Islamic Boarding School is still not well implemented, because the BK teacher is not from a BK background, so the BK teacher does not understand the existing counseling techniques, especially the problem of multi-cultural clients, teachers BK does not understand the client culture and the client culture is more similar, while clients come from a variety of areas that must be understood by BK teachers, and students' problems often originate from different cultures. The BK teacher should understand the client's culture so that it is easier to know what causes the client's problem and the client can find a solution to the problem. So as to be able to carry out multi-cultural counseling in a professional manner so that clients are able to understand themselves and alleviate the problems they face so that from KES-T (disrupted effective day-to-day life) to KES (daily effective life).